2007
DOI: 10.1080/15421400701206139
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Laser Scanning Microscopic Observation of Polymer-Stabilized Blue Phase I

Abstract: The structure of the polymer-stabilized blue phase I with a cubic structure of the order of optical wavelength was observed by the confocal laser scanning microscope. The spacing of a striped pattern observed in the (110) plane of the polymer-stabilized blue phase I was a couple of hundred nm, which agreed to the interval of the ordered double twisted cylinders estimated based on a well-known model of blue phase I with O 8 symmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
3
7
0
Order By: Relevance
“…(f)). This very simple experiment confirms the results of earlier, very sophisticated microscopic studies, which indicated that the polymer network is located at the positions of the BP disclinations (Fig. (e)).…”
Section: Blue Phase Stabilizationsupporting
confidence: 91%
See 1 more Smart Citation
“…(f)). This very simple experiment confirms the results of earlier, very sophisticated microscopic studies, which indicated that the polymer network is located at the positions of the BP disclinations (Fig. (e)).…”
Section: Blue Phase Stabilizationsupporting
confidence: 91%
“…The latter systems may be useful for storage applications, but show no electro‐optic response. The largest BP temperature range for electrically addressable BPs is obtained for polymer‐stabilized LCs . The total monomer concentration is typically between 8% and 15% by weight.…”
Section: Blue Phase Stabilizationmentioning
confidence: 99%
“…As a host nematic liquid crystal (host LC), a mixture of fluorinated nematic liquid crystals (JC1041‐XX, JNC Co., Δ n = 0.142, Δ ϵ = 5.7 at 25 °C)/4‐cyano‐4′‐pentyl biphenyl (5CB, Aldrich, Δ n = 0.19, Δ ϵ = 11 at 25 °C) = 1:1 were used 8–16, 49, 50. A dendron molecule was newly synthesized to enlarge the BP temperature range.…”
Section: Methodsmentioning
confidence: 99%
“…Liquid crystalline blue phases (BPs) are one of the candidates for tunable photonic crystals, possessing an optical stopband in the visible wavelength range due to their lattice periods of several hundred nm, which can be continuously shifted by electric fields 4–7. Though originally BPs appeared over a very narrow temperature range (typically about 1 °C) between isotropic phase (Iso) and chiral nematic phase (N*), polymer‐stabilized blue phases (PSBPs) have been found to show a large temperature range of stable BPs of more than 60 °C; they also show excellent performance for application to liquid crystal displays, including fast electro‐optical responses of less than 1 ms (conventional nematic phase shows several ms in response time) and a large Kerr constant 8–24. Also, BPs show a great benefit compared to N*, which shows a 1D stopband as a photonic crystal,25, 26 because the lasing threshold energy needed to excite the BPs is much lower than that of N* 27–29.…”
Section: Introductionmentioning
confidence: 99%
“…If the positions of dots do not change entirely with depth, the detecting image should come from the reflection at the interface between the cover glass and sample. 2 However, it is noted that the positions of dots slightly moved, it means that the image comes from bulk structure of the sample.…”
Section: Confocal Laser Scanning Microscope Z-scanning Z-scanningmentioning
confidence: 99%